The temporal volatility of nonfinancial performance and stock return - Sascha Raithel (Risk Management, 2025)
Uncertainty about input factors and potential outcomes characterize almost any business-relevant decision. By using signals about uncertainty such as historical performance volatility (temporal volatility) as inputs, investors adjust their expectation about future firm value. This decision calculus has found broad empirical support concerning the temporal volatility of financial performance. However, concerning the temporal volatility of nonfinancial performance, research offers only limited insights. This study addresses this research gap. Two observational studies (N1 = 513 and N2 = 348) provide empirical evidence that investors downweigh changes in nonfinancial performance—measured as brand perception in one study and customer satisfaction in the other—when updating their beliefs about future firm value (as reflected by stock returns) if the volatility of historical nonfinancial performance is high.
Keywords: G11; G41; 330; Nonfinancial performance; Firm value; Stock return; Volatility; Uncertainty